The Expected Rate of Credit Losses on Banks' Loan Portfolios - Harris, Trevor S.; Khan, Urooj; Nissim, Doron (The Accounting Review, 2018)
ABSTRACT Estimating expected credit losses on banks' portfolios is difficult. The issue has become of increasing interest to academics and regulators with the FASB and IASB issuing new regulations for loan impairment. We develop a measure of the one-year-ahead expected rate of credit losses (ExpectedRCL) that combines various measures of credit risk disclosed by banks. It uses cross-sectional analyses to obtain coefficients for estimating each period's measure of expected credit losses. ExpectedRCL substantially outperforms net charge-offs in predicting one-year-ahead realized credit losses, and reflects nearly all the credit loss-related information in the charge-offs. ExpectedRCL also contains incremental information about one-year-ahead realized credit losses relative to the allowance and provision for loan losses and the fair value of loans. It is a better predictor of the provision for loan losses than analyst provision forecasts, and is incrementally useful beyond other credit risk metrics in predicting bank failure up to one year ahead.